Effects of Sb2O3 on the Mechanical Properties of the Borosilicate Foam Glasses Sintered at Low Temperature. (28th December 2014) - Zhai, Chenxi; Li, Zhe; Zhu, Yumei; Zhang, Jing; Wang, Xiuduo; Zhao, Lejun; Pan, Liuming; Wang, Pengfei
Abstract : The physical properties and microstructure of a new kind of borosilicate foam glasses with different Sb2 O3 doping content are comprehensively investigated. The experimental results show that appropriate addition of Sb2 O3 has positive impact on the bulk porosity and compressive strength of the foam glass. It is more suitable in this work to introduce 0.9 wt.% Sb2 O3 into the Na2 O-K2 O-B2 O3 -Al2 O3 -SiO2 basic foam glass component and sinter at 775°C. And the obtained foam glasses present much more uniform microstructure, large pore size, and smooth cell walls, which bring them with better performance including a lower bulk density, low water absorption, and an appreciable compressive strength. The microstructure analysis indicates that, with the increase of the content of Sb2 O3 additives, the cell size tends to increase at first and then decreases. Larger amounts of Sb2 O3 do not change the crystalline phase of foam glass but increase its vitrification. It is meaningful to prepare the foam glass at a relatively low temperature for reducing the heat energy consumption.